2010
DOI: 10.1093/molbev/msq325
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Voltage-dependent Na+ Channel Gene Family in Early Tetrapods Coincided with the Emergence of Terrestriality and Increased Brain Complexity

Abstract: Mammals have ten voltage-dependent sodium (Nav) channel genes. Nav channels are expressed in different cell types with different subcellular distributions and are critical for many aspects of neuronal processing. The last common ancestor of teleosts and tetrapods had four Nav channel genes, presumably on four different chromosomes. In the lineage leading to mammals, a series of tandem duplications on two of these chromosomes more than doubled the number of Nav channel genes. It is unknown when these duplicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 52 publications
5
43
0
Order By: Relevance
“…It was suggested that expansion of Na V subtypes in vertebrates correlated with increased neuronal complexity (Zakon et al, 2011) and it is tempting to hypothesize that the same might be true for the expansions in Cnidaria. However, a functional approach is required for testing this hypothesis.…”
Section: Open Questions Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that expansion of Na V subtypes in vertebrates correlated with increased neuronal complexity (Zakon et al, 2011) and it is tempting to hypothesize that the same might be true for the expansions in Cnidaria. However, a functional approach is required for testing this hypothesis.…”
Section: Open Questions Challenges and Future Directionsmentioning
confidence: 99%
“…In the human genome there are 10 genes encoding Na V s (Na V 1.1-Na V 1.9 and Na X ). It is thought that in the common ancestor of vertebrates only one Na V 1 gene was present, which underwent two rounds of duplication in the basal vertebrate and further duplication and diversification in teleosts and tetrapods (Widmark et al, 2011;Zakon et al, 2011). As in the case of K V s discussed before, the finding of such a diversity of sodium channels in a sea anemone was highly unexpected (Gur Barzilai et al, 2012).…”
mentioning
confidence: 98%
“…13) (Hellsten et al, 2010;Zakon et al, 2011). Detailed description of the development of the methods in paper III can be found in the methods section ("Finding a gene in an unsequenced genome" and "Alter the expression level of a SCN2A ortholog").…”
Section: Resultsmentioning
confidence: 99%
“…The gene sequences for six Na v channels from X. tropicalis are partly known and can be retrieved at www.xenbase.org. (Gilchrist, 2012;Hellsten et al, 2010;Zakon et al, 2011) To explore the possibility to target specific Na v channel sequences in X. laevis using primers designed for X. tropicalis, tissues from X. laevis with known expression of different Na v channel genes (SCNA genes) were collected after the frogs were sacrificed (brain, heart, and skeletal muscles). Total mRNA was extracted from the tissues and cDNA created.…”
Section: Finding a Gene In An Unsequenced Genomementioning
confidence: 99%
“…Na V s subsequently evolved from Ca V in apoikozoa, a phylum comprising animals and the closely related choanoflagellates (5). In tandem, the emergence of the sodium selectivity and fast (sub-millisecond) voltagedependent gating served as functional prerequisites for complex action potential firing and neuronal complexity (6). Further, five isoforms of sodium channel β-subunits have been identified, namely, β1, β2, β3, β4 and splice variant β1b (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%